2018
DOI: 10.1007/s40003-018-0309-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Establishment Techniques and Maturity Duration of Pigeon Pea Cultivars on Yield, Water Productivity and Properties of Soil

Abstract: India is the leading country with respect to area and production of pulse crop pigeon pea (Cajanus cajan L.). However, the productivity of this crop is too low and almost static for the last five decades due to cultivation of long-duration cultivars that are prone to climatic variations causing temporary water logging, drought and frost. Proper selection of the cultivar and use of appropriate crop establishment may help in enhancing productivity. Therefore, a field investigation was carried out for 3 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Similarly, net returns were significantly higher with BBF and ZT compared with CT. Additional net returns of wheat were 157 US$ with ZT and 200 US$ with BBF compared with total net returns of 843 US$ ha -1 with CT, respectively. Consistency of our result was due to higher net returns and reduction in cost of cultivation and higher yield with BBF and ZT [25,27]. The B/C ratio of wheat with different sowing techniques is also significantly higher under BBF (2.6) followed by ZT (2.4), MT (1.9) and CT (1.7), respectively.…”
Section: Economicssupporting
confidence: 72%
See 3 more Smart Citations
“…Similarly, net returns were significantly higher with BBF and ZT compared with CT. Additional net returns of wheat were 157 US$ with ZT and 200 US$ with BBF compared with total net returns of 843 US$ ha -1 with CT, respectively. Consistency of our result was due to higher net returns and reduction in cost of cultivation and higher yield with BBF and ZT [25,27]. The B/C ratio of wheat with different sowing techniques is also significantly higher under BBF (2.6) followed by ZT (2.4), MT (1.9) and CT (1.7), respectively.…”
Section: Economicssupporting
confidence: 72%
“…The crop sowing techniques of ZT and BBF increased OC from 0.07 and 0.06 g kg -1 , IR 0.9 and 1.0 mm h -1 compared with values of CT treatment, respectively. Another study showed that raised bed planting helps to improve soil organic matter and physical characteristics owing to surface retention of more residues compared to other sowing techniques [27], whereas continuous tillage degrades soil organic matter which reduces soil fertility as well as structural stability [9,24]. The lower BD values under ZT due to higher root mass in surface soil and decomposition of crop residues [26,27].…”
Section: Soil Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Indian subcontinent alone contributes nearly 92% of the total pigeonpea production of the world , Kumar et al, 2016. In 2013-14, productivity was around 25% lower (730 kg ha -1 ) than the world average (910 kg ha -1 ) (Singh et al, 2018). Productivity of pigeonpea, however, continues to be low, as this crop are generally grown in rainfed areas under the poor management and face various kinds of biotic and abiotic stresses , Kumar et al, 2015a,b and Choudhary et al, 2013.…”
Section: Introductionmentioning
confidence: 99%